Prevalence and Clinical Characteristics including Patterns of Antihypertensive Drug Administration of the Different Home Blood Pressure Phenotypes in Treated Hypertensive Patients - Chavalit Chotruangnapa; Tossaporn Thammarux; Piyawan Thongdang (International Journal of Hypertension)
Quality and quantity of home blood pressure (BP) control are important for optimizing hypertensive treatment. The prevalence and associated clinical characteristics of the different home blood pressure phenotypes in treated hypertensive patients were not elucidated. This study was conducted in Siriraj Hospital, Thailand from 2019 to 2020. We included treated hypertensive patients with ≥1 antihypertensive drug and had self-home BP measurement data. Both traditional (office BP < 140/90 mmHg and home BP < 130/80 mmHg) and new BP targets (office and home BP < 130/80 mmHg) were used for the classification of BP phenotypes. Home BP phenotypes consisted of controlled hypertension (all home BPs achieved home BP targets), isolated uncontrolled morning hypertension (MoHT) (only morning BP was above home BP targets), isolated uncontrolled evening hypertension (EHT) (only evening BP was above home BP targets), and combined morning-evening uncontrolled hypertension (MoEHT) (all home BPs were above home BP targets). Our study included 1,406 patients. The total mean age was 62.94 ± 13.97 years. There were 39.40% men. The prevalence of each home BP phenotype (by traditional BP target) was 55.76%, 12.66%, 7.40%, and 24.18% in controlled (home) hypertension, MoHT, EHT, and MoEHT, respectively. Classical BP control status was 35.21% well-controlled hypertension, 30.01% white-coat uncontrolled hypertension, 9.74% masked uncontrolled hypertension, and 25.04% sustained uncontrolled hypertension. The multivariable analysis showed the significantly associated factor of MoHT was the presence of previous cardiovascular disease (adjusted OR 5.54, 95% CI (2.02–15.22); p value = 0.001). Taking once-daily long-acting antihypertensive drugs in the morning were significantly associated with both EHT (adjusted OR 0.20, 95% CI (0.05–0.82); p value = 0.025) and MoEHT (adjusted OR 0.20, 95% CI (0.04–1.00); p value = 0.049). These results were consistent in groups classified by new home BP target <130/80 mmHg.